URBAN TOURISM AND UNIVERSITY SPORTS. CASE STUDY ON THE IMPACT OF THE NATIONAL UNIVERSITY FOOTBALL CHAMPIONSHIP ON THE DESTINATION OF ORADEA, ROMANIA - Herman, Grigore Vasile; Bulz, Gheorghe Codrut; Herman, Mariana Laura; Anca, Sab?u; Bulz, Andrada Maria; Tofan, George-Bogdan; Sandra, Mihai (Editura Universitatii din Oradea, 2025)
Since the second half of the 20th century, major changes have occurred worldwide in the perception of sport and sports tourism. Economic development and technical progress in every field have led to the emergence of new sports, which have become particularly attractive, especially for the young population. Therefore, sports tourism is becoming one of the expanding forms of tourism, which involves a multitude of relationships between tourists engaged in different activities (physical exercise, sports competitions, adventure tourism, sports entertainment and cultural exchange activities), on the one hand, and the tourist destination, on the other. In this study, we propose an analysis of the relationships between the University Football Championship, 2023 Edition, and tourism in the host destination, Oradea Municipality. This was possible after consulting, through the survey method, the members of the football teams from eight university centers in Romania, who participated in the University Football Championship, 2023 Edition, in Oradea. The results obtained were quantified after calculating two synthetic indicators, namely: the value of the sports index, which takes into account four qualitative criteria (quality of the game, quality of interaction, quality of the result and quality of the physical environment), respectively the value of the tourist index, also related to four qualitative criteria (tourist experience, tourist satisfaction, recommendation intention and return intention). In the case of both indicators and following their correlation, high average values were recorded, which can be attributed to the exceptional playing conditions offered by the organizer-the University of Oradea, respectively to the particularly favorable perception and satisfaction gained by the participants, following visits to the tourist attractions in Oradea Municipality, which proves, without a doubt, that the settlement on the banks of the Cri?ul Repede is one of the favorite tourist destinations in Romania. © 2025, Editura Universitatii din Oradea. All rights reserved.
Keywords: college football championship; Oradea tourist destination; tourist experience; tourist intention; tourist perception; tourist satisfaction; university sport